2018
DOI: 10.1002/cncr.31411
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of tyrosine kinase inhibitors in chronic myeloid leukemia: Recommendations for clinical practice from the French Chronic Myeloid Leukemia Study Group

Abstract: This work presents consensus statements with the aim of guiding physicians and biologists by means of pragmatic recommendations for safe TKI discontinuation in daily practice. Cancer 2018;124:2956-63. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
106
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(108 citation statements)
references
References 41 publications
(96 reference statements)
1
106
1
Order By: Relevance
“…11 Indeed, ESMO recommends at least 5 years of TKI therapy combined with ≥2 years of DMR before TKI discontinuation, 13 while the French CML Study Group requires at least 2 years of MR 4.5 before discontinuation in order to reach the TFR. Moreover, a great uncertainty still remains for the level of MR. 12 Considering the pivotal clinical trials concerning TKI discontinuation, in EURO-SKI study, a threshold of 3.1 years of F I G U R E 4 Treatment-free remission (TFR) curves according to MR class measured by RT-qPCR at the time of discontinuation. The red curve represents patients discontinued with MR 4.0 , and the black curve patients with MR 4.5-5.0 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Indeed, ESMO recommends at least 5 years of TKI therapy combined with ≥2 years of DMR before TKI discontinuation, 13 while the French CML Study Group requires at least 2 years of MR 4.5 before discontinuation in order to reach the TFR. Moreover, a great uncertainty still remains for the level of MR. 12 Considering the pivotal clinical trials concerning TKI discontinuation, in EURO-SKI study, a threshold of 3.1 years of F I G U R E 4 Treatment-free remission (TFR) curves according to MR class measured by RT-qPCR at the time of discontinuation. The red curve represents patients discontinued with MR 4.0 , and the black curve patients with MR 4.5-5.0 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the TKI discontinuation strategy cannot be considered as optimized in this setting. Clinically relevant questions were addressed also by the French CML Study Group, which recently published the recommendations on discontinuation of TKI in CML for clinical practice . They remark the importance of determining the best level of DMR for TKI discontinuation.…”
Section: Introductionmentioning
confidence: 99%
“…The results of several phase 2 single-arm TFR studies, [36][37][38][39][40][41][42][43][44] individual experience, patient will, as well as commercial pressure, may bias the choice of treatment. 13,24,26,[45][46][47][48] For these reasons, the CML Working Party (WP) of Gruppo Italiano Malattie EMatologiche dell'Adulto (GIMEMA; Italian Group for Hematologic Diseases of the Adult) has developed a project that has involved the representatives of 50 hematologic centers, with the purpose of suggesting a treatment policy aiming to the achievement of TFR.…”
Section: Introductionmentioning
confidence: 99%
“…Achievement of DMR is important for patients with CML‐CP because these responses are associated with improved long‐term outcomes compared with lesser levels of response, including higher rates of event‐free survival and overall survival, and a lower risk of disease progression (Etienne et al , ; Hehlmann et al , ). DMR has recently become the patient selection criterion of choice to achieve a new goal in CML therapy: TKI discontinuation and treatment‐free remission (Rea et al , ). Results from the large ENEST1st study, which evaluated DMR (MR 4 ) as the primary endpoint, have confirmed the high cumulative rates of DMR achieved with first‐line nilotinib therapy (55·5% after 24 months of treatment) (Hochhaus et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Dasatinib and nilotinib were both approved in the United States and the European Union in 2011 for newly diagnosed patients with CML‐CP; however, nilotinib is the only second‐generation TKI reimbursed in this setting in France and imatinib remains the most frequently used TKI (Etienne et al , ). First‐line nilotinib therapy offers several advantages compared to imatinib, such as early reduction of molecular residual disease burden, significant reduction of progression rate, and a higher rate of deep molecular responses (DMRs) which represents a criterion for treatment discontinuation (Breccia et al , ; Rea et al , ). The first results from the single‐arm, phase II Evaluating Nilotinib Efficacy and Safety in clinical Trials (ENEST) freedom study showed that a clinically significant percentage of CML‐CP patients (51·6%) with sustained DMR on frontline nilotinib therapy and a median treatment duration of 43·5 months were able to remain in major molecular response (MMR) and treatment‐free remission for more than 48 weeks after stopping nilotinib (Hochhaus et al , ).…”
mentioning
confidence: 99%